2019
DOI: 10.21203/rs.2.13303/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Distraction Techniques on Pain and Stress during Labor: A Randomized Controlled Clinical Trial

Abstract: Background The aim of this study was to determine the effect of distraction techniques on labor pain and stress (primary outcomes), fear of childbirth, and length of delivery stages (secondary outcomes). Methods A randomized controlled clinical trial was conducted on 68 pregnant women. Participants were allocated into two intervention and control groups by blocked randomization. Participants in the intervention group received distraction techniques in four sessions. Questionnaires of Fear of Childbirth (W-D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Frey et al (2019) also demonstrated that wearing 360-degree eyewear while viewing virtual reality video during the first stage of labor in shortening delivery length probably. Opposite to this, the results of our study in contrast to Amiri, et al, (2019), who clarified that there was no statistically significant difference in total length and duration of labor.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Frey et al (2019) also demonstrated that wearing 360-degree eyewear while viewing virtual reality video during the first stage of labor in shortening delivery length probably. Opposite to this, the results of our study in contrast to Amiri, et al, (2019), who clarified that there was no statistically significant difference in total length and duration of labor.…”
Section: Discussioncontrasting
confidence: 93%
“…The findings of this study were comparable to those of Ebrahimian & Bilandi's (2020) study on "Comparations of the effects of watching virtual reality videos and chewing gum on the length of delivery phases and maternal labor satisfaction." Moreover, Amiri, et al, (2019) in "The influence of distraction tactics on pain and stress during labor" found no appreciable differences in the sociodemographic features of the two groups.…”
Section: Discussionmentioning
confidence: 93%
“…It was observed that women in the experimental group were able to cope with labor pain more effectively. Studies have shown that interventions by healthcare professionals that provide physical and emotional comfort (holding the woman’s hand, massage, changing position, allowing taking a warm shower, ensuring hygiene, saying words of appreciation, encouraging, making eye contact, appreciating, helping focus on positive things, providing spiritual care, breathing and relaxation techniques, and distraction) are effective in the management of labor pain (Amiri et al, 2019; Bohren et al, 2016; Steel et al, 2015 ). Our study results are consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%